Kajian Awal Terhadap Ketersediaan LKPD Berbasis Inkuiri Di Sman 5 Pekanbaru - Gustriya, Reni; Mellisa; Hidayati, Nurkhairo (CV. SINAR HOWUHOWU, 2026)
This study aims to examine the availability and use of inquiry-based student worksheets (LKPD) in Biology learning at SMAN 5 Pekanbaru. A descriptive quantitative approach supported by qualitative data was applied. The participants consisted of 38 tenth-grade students and one Biology teacher. Data were collected through student perception questionnaires, short-answer tests, interviews, and worksheet documentation. The data were analyzed using descriptive statistics and qualitative analysis. The results indicate that LKPD availability is categorized as good; however, the implementation of inquiry principles remains limited. The worksheets tend to be conventional and are mainly used as supporting learning materials. Therefore, the development of more structured inquiry-based worksheets is needed to support student-centered Biology learning.